Investigating challenges in conducting micro-teaching among English education (ED) undergraduates in a Malaysian private university - Magenthiran, Shasmita (2023)
Micro-teaching is a cutting-edge approach to training in which a student-teacher or teacher-trainer teaches a small class of pupils for a brief period of time. The goal of this is to improve teachers' abilities. This method, which focuses on a single ability at a time, has worked well. The goal of this report is to investigate challenges in conducting microteaching among English Education (ED) undergraduates in a Malaysian private university. Research objectives in this research are to identify the challenges faced by English Education (ED) undergraduates of a Malaysian private university in conducting micro-teaching and to critically analyze the ways in overcoming the challenges in conducting micro-teaching, recommendations by English Education undergraduates of a Malaysian private university. In this study, a mixed-method technique also known as the utilization of both quantitative and qualitative methods is employed. A survey questionnaire and open-ended interview questions were among the research's instruments. The first highest mean and SD is “I feel microteaching is a disheartening situation when conducting it for the first time in the class” (M=3.4 , SD = 2.921). Twenty-eight participants answered strongly agree and agree, that shows this answered how disheartening micro-teaching is. Students agreed that conducting microteaching for the very first time made them nervous as it is a new experience for them. A larger sample size should be used for the study in order to provide the researcher with more insightful study data and a better understanding of the data.